Identifying discrepancies between clinical practice and evidence-based guideline in recurrent pregnancy loss care, a tool for clinical guideline implementation - A. Youssef; E.E.L.O. Lashley; N. Vermeulen; M.L.P. van der Hoorn (BMC, 2023)
Abstract Background Practice variation in recurrent pregnancy loss (RPL) care is common. International guidelines vary in their recommendations for the management of RPL couples, which could lead to an increase of cross border reproductive care. Currently, the Dutch RPL guideline is being adapted from the European Society for Human Reproduction and Embryology (ESHRE) guideline. We aim to identify discrepancies between RPL guidelines and RPL practice. These discrepancies could be considered in the development of a new guideline and implementation strategies to promote adherence to new recommendations. Methods A nationwide survey on the management of RPL patients was conducted across all 107 hospital-based obstetrics and gynaecology practices in the Netherlands. The survey was sent via the Dutch Society for Obstetricians and Gynaecologists to all affiliated clinicians. The questionnaire consisted of 36 questions divided in four sections: clinician's demographics, RPL definition, investigations and therapy. The data were compared to the recommendations given by the Dutch national guideline and the most recent guideline of the ESHRE. Results All hospital-based practices (100%; n = 107) filled in the online questionnaire. The majority of respondents defined RPL similarly, as two or more pregnancy losses (87.4%), not obligatory consecutive (93.1%). More than half of respondents routinely perform thrombophilia screening ( 58%), although not advised by the ESHRE, while thyroid function (57%), thyroid auto-immunity (27%) and β2-glycoprotein antibodies (42%) in the context of antiphospholipid syndrome (APS) are recommended but investigated less often. Regarding parental karyotyping, 20% of respondents stated they always perform parental karyotyping, without prior risk assessment. because of RPL. Treatment for hereditary thrombophilia was frequently (43.8% (n = 137)) prescribed although not recommended. And finally, a considerable part (12-16%) of respondents prescribe medication in case of unexplained RPL. Conclusion While many clinicians perform investigations recommended by the ESHRE, there is a considerable variation of RPL practice in the Netherlands. We identified discrepancies between RPL guidelines and RPL practice, providing possibilities to focus on multifaceted implementation strategies, such as educational intervention, local consensus processes and auditing and feedback. This will improve the quality of care provided to RPL patients and may diminish the necessity felt by patients to turn to multiple opinions or cross border reproductive care.